Financial Services: Unlocking the Potential for Export Diversification - United Nations Conference on Trade; Development (United Nations, 2023)
The services sector presents an opportunity for African countries to diversify their exports through two key facets: (a) the use of innovation and technology in the services sector can strengthen productive capacities, leading to high-quality and more diversified exports of goods; and (b) African countries can diversify exports through intensifying forward and backward linkages with services sectors and increasing export of services. This policy brief, based on the EDAR 2022, presents recommendations on how the roles of financial services and private businesses can be leveraged to strengthen productive capacity and diversify into high-quality exports.